“Oh, I go on a whim.” Mobility in the everyday lives of the elderly living in the countryside - Wilde, Mathias (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
Since the problematisation of the demographic change, mobility research has taken a stronger interest in the mobility of the elderly. It’s here that the research is often influenced by the needs of transportation planning and policy. This often results in framing the mobility of elderly people as a technical or organisational problem. However, if mobility viewed as a social phenomenon, the question must be asked: How are mobility und the routines of daily life intertwined? The paper approaches the everyday mobility of the elderly from an agent-centred perspective. To provide an understanding of how the elderly living in rural areas view mobility and integrate it into their daily lives is the main aim of the paper. Using the results of a qualitative study, this paper emphasises causes leading to travel decisions and illustrates the importance of emotions and the functional aspect of maintaining health. Most importantly, this paper will show the value of social contacts. Even if everyday needs, such as grocery shopping or a trip to the doctor, prove to be the reason for mobility, occurrences of social interaction are which count and which influence the lives of elderly people living in the countryside. Finally, based on the findings, the implications for transportation planning and policy will be outlined and explored.